Epidemiology and Hemato-Biochemical Changes in Mange Infested Goats - Shah, Kuntal S.; Mandali, Ghanshyam C.; Rao, Neha; Patel, Ashish C.; Panchal, Ronak P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Mange in goats is a contagious skin disease characterized by crusty, pruritic dermatitis and patchy/generalized alopecia. It is caused  by a variety of parasitic mites burrowing in or living on the skin. For the present study, 30 mange-infested goats of Surti and Marwari  breeds were selected from those presented at the Veterinary Clinical Complex of the College and from surrounding villages of Anand,  and six goats from the University farm were taken as a healthy control group. The maximum prevalence of sarcoptic mange was found  in the age group of 1-2 years of age (60.00%), followed by >2 years (26.67%) and
Keywords: Hemato-biochemical alterations; Goat; Mange infestation; Prevalence